Relationship between Nutritional Status and Lymphocyte Count in Children with Dengue Fever at Dr. Pirngadi Regional Hospital, Medan - Sonya Maranata Situmorang; Susi Sembiring; Joice Sonya G Panjaitan (Jurnal EduHealth, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. Nutritional status is thought to play a role in the body's immune response to infection, including in regulating the number of lymphocytes that play a role in the immune system. However, the relationship between nutritional status and lymphocyte count in children with DHF still needs further study. This study aims to analyze the relationship between nutritional status and lymphocyte count in children with DHF at Dr. Pirngadi Hospital, Medan. This study used a cross-sectional design with secondary data from medical records of pediatric patients with DHF at Dr. Pirngadi Hospital, Medan for the period 2021-2022. The study sample was selected using the consecutive sampling method with a total of 35 samples. Data analysis was carried out using the Chi-Square test to determine the relationship between nutritional status and lymphocyte count. The majority of study subjects had normal nutritional status (80%), while 14.3% were malnourished and 5.7% were overweight. Most subjects had lymphocytosis (77.1%), while 20% had normal lymphocyte counts, and 2.9% had lymphocytopenia. Bivariate analysis showed a significant relationship between nutritional status and lymphocyte count (p=0.010).There is a significant relationship between nutritional status and lymphocyte count in children with DHF at Dr. Pirngadi Medan Regional Hospital. Children with malnutrition tend to have lower lymphocyte counts than children with normal or more nutrition.